Implementasi Budaya Organisasi Dalam Peningkatan Kinerja Pegawai di Kantor Pencarian dan Pertolongan (BASARNAS) Kelas B Nias - Erwin Sah Putra Zebua; Sukaaro Waruwu; Peringatan Harefa; Fatolosa Hulu (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the implementation of organizational culture in improving employee performance at the Nias Class B Search and Rescue Office (BASARNAS). Organizational culture plays a crucial role in shaping employee behavior, motivation, and productivity, especially in public service institutions such as BASARNAS. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and document analysis related to organizational culture at BASARNAS Class B Nias. The main respondents were BASARNAS employees and management, selected by purposive sampling. The results of the study indicate that the implementation of organizational culture at BASARNAS Class B Nias has a positive impact on employee performance. A strong organizational culture, especially one that emphasizes values ​​such as cooperation, responsibility, and innovation, is a determining factor in creating a conducive work environment. The active involvement of management in promoting and maintaining the culture also plays a vital role in increasing employee morale and dedication. However, this study also identified several challenges in implementing organizational culture, including resistance to change from some employees and the incompatibility of cultural values ​​with local characteristics. Therefore, this study provides strategic recommendations to improve the effectiveness of organizational culture implementation, such as developing training programs, communicating cultural values ​​more effectively, and strengthening collaboration between management and employees.